(untitled) (Agricultural Engineering, 2016)
Currently, many countries are establishing goals for substituting fossil fuels with biomass. This global trade in solid biofuels, which is to some extent already taking place, will have a major impact not only on other commodity markets like vegetable oils or animal fodder but also on the global land use change and on environmental impacts. It demonstrates the strong but complex link between biofuels production and the global food market, it unveils policy measures as the main drivers for production and use of biofuels and it analyzes various sustainability indicators and certification schemes for biofuels with respect to minimizing the adverse effects of biofuels. Biomass is seen as a very promising option for fulfilling the environmental goals defined by the European Commission as well as various national governments. We have measured selected physicochemical properties of several the most common oilseeds and the residue materials in the form of cakes, moisture, fat, heat of combustion, the calorific value and ash content. The results showed that the considered plants and waste derived therefrom can be a good energy source. Examples include sunflower oilcake, sesame, pumpkin and rapeseed cake, for which the calorific value amounted to respectively: 28.17; 27.77; 26.42 and 21.69 MJ·kg−1.